Household Air Pollution and Behavioral Risk Factors for Acute Respiratory Infections in Toddlers: a Case-Control Study in Maros, Indonesia - Mulyadi Mulyadi; La Taha La Taha; Budirman Budirman; Ronny Muntu (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Acute Respiratory Infection (ARI) remains a leading cause of morbidity among toddlers in Indonesia, with household environmental and behavioral factors playing a critical role in its transmission. This study aimed to analyze the risk factors associated with ARI incidence among toddlers in the working area of the Bantimurung Community Health Center, Maros Regency. An analytical observational study with a case-control design was conducted involving 158 toddlers (79 cases and 79 controls). Data were collected through structured interviews and observation, and analyzed using binary logistic regression to estimate crude and adjusted odds ratios (OR) with 95% confidence intervals (CI). The results showed that four variables were significantly associated with ARI incidence: occupancy density (adjusted OR = 4.137; 95% CI: 1.893–9.040; p < 0.001), family members’ smoking habits (adjusted OR = 2.763; 95% CI: 1.289–5.925; p = 0.009), use of mosquito repellents (adjusted OR = 4.480; 95% CI: 2.045–9.818; p < 0.001), and personal hygiene (adjusted OR = 2.455; 95% CI: 1.154–5.224; p = 0.020). Nutritional status (p = 0.074) and immunization history (p = 1.000) were not statistically significant. The use of mosquito repellents was identified as the strongest risk factor, indicating that toddlers in households using mosquito repellents were 4.48 times more likely to develop ARI. Interventions should prioritize reducing exposure to indoor air pollutants, particularly from mosquito repellent combustion, and promoting smoke-free and hygienic household environments.